Extraction and Proximate Study of Sansevieria Trifasciata L. As Fibre Source for Textile and Other Uses (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Natural fibres are getting importance for their sustainable development in their uses in mitigation of climate change and ecological balance. A fibre extraction retting method is formulated and proximate chemical composition and various physical properties such as tensile strength, elongation, diameter along with fibre, cellulose, lignin and ash content were determined. This preliminary observation indicates its potential to be used as a source of fibre for textile and non-textile uses such as woven, nonwoven, composite, blanded and a good source of α-cellulose, microcrystalline cellulose, nano-cellulose and lignin-based products.J. Asiat. Soc. Bangladesh, Sci. 46(2): 155-162, December 2020